Impact of Blockchain to Secure E-Banking Transaction - Das Nath, Mausumi; Bhattasali, Tapalina (International Journal of Computer Sciences and Engineering, 2025)
Although E-banking provides its customers a wide range of services at anytime and from anywhere, most of the research studies have indicated that security is the major concern to adopt it without any doubt. As digital world is full of known and unknown cyber threats, there is a real need to protect sensitive records from misuse. Blockchain is a new technology that just steps in to solve the issues. It is basically a linked list of blocks (public ledgers) that records data in hash functions with timestamps to store it anonymously with other participants within the chain. It eliminates third party dependency required for the traditional banking, which in turn reduces the probability of central point vulnerability. Data manipulation is impractical due to use of one-way hash function. There is no requirement of designing distributed trust model as all transactional data are verified with every relevant stakeholder. It has been studied here how Blockchain technology can be used for E-banking scenarios using hash algorithm along with nonce and what is its impact on the society to transfer financial data. However, there are still a few issues associated with Blockchain that need to be addressed before implementing it in real-life.